Pendekatan Farmakogenomik Dalam Pengembangan Obat Baru - Radji, Maksum (UI Scholars Hub, 2005)
The human population is heterogeneous and consists of populations of immense ethnic diversity. There are considerable allelic differences between human popula-tions as well as individuals within each ethnic group as a result of molecular hetero-geneity of the genome. This, in turn, is responsible for differential allelic expression of genes endowing them with polymorphic characters. The molecular diversity within genes is responsible amongst others, of disease resistance or susceptibility or for that matter drug response. Pharmacogenomics is the key to the understanding of differ-ential drug response in different patients in relation to genetic constitution. The revelation of such information at the molecular level would assist the pharmaceuti-cal industry to address a therapy directed to each individual. The objective of this article is to understand the nuances of the genetic repertoire and correlate it with disease gene identification, genes that have been or can be used as drug targets, identify candidate genes for drug development and recent trends in drug discovery.